Improving learning outcomes through discovery learning on the human respiratory system material - Indriani, Cecilia; Hidayat, Saleh; Astriani, Meli (Journal of Education and Learning (EduLearn), 2025)
Based on the results of observations at Madrasah Aliyah Negeri (State Islamic Senior High School) 1 Palembang, it was found that there were problems in learning biology; namely, the daily test scores for class XI science 2, semester 1 for the 2021/2022 around 30% of students have scored above the minimum completeness criteria (MCC) and the learning outcomes of school year 2020/2021 it shows only 29% or nine students out of 31 students achieve scores above the MCC. This research aims to improve student's learning outcomes in class XI science 2 using the discovery learning model. This type of research is called classroom action research (CAR) and consists of two cycles. The results showed that applying the discovery learning model can improve students' learning outcomes. The learning outcomes of the knowledge domain in the first cycle obtained a percentage of students' completeness of 53.33% (average value was 68). In contrast, in the second cycle, there was an increase in students' completeness of 83.33% (average value was 81). Applying the discovery learning model implemented at Madrasah Aliyah Negeri 1 Palembang, can improve learning outcomes. The increased learning outcomes were accompanied by increased student activity in asking, answering, and discussing. The percentage of learning outcomes in the first cycle of cognitive aspects from 53.33% of students who obtained a score above the MCC with an average score of 68 increased by 83.33% with an average score of 81 in Cycle II.